EKSTRAK ETANOL TERIPANG PASIR (Holothuria scabra) DALAM MEMPERBAIKI KERUSAKAN USUS HALUS MENCIT (Mus Musculus) YANG TERPAPAR KALIUM BROMAT MELALUI PENGAMATAN GAMBARAN HISTOPATOLOGI MENCIT - Hanna Kalorbobir; Theopilus Watuguly (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: In Indonesia, traditionally sea cucumber (Holothuria scabra) is often used as a drug for uric acid. A study has been conducted on the effect of giving sandy cucumber extract (Holothuria scabra) to microscopic images of the small intestine of mice (Mus muculus) induced by potassium bromate. Method: This study used a small intestine sample of 2-3 months old male mice weighing + 20-30gr for 15 mice used in the study, divided by 5 groups, ie group I was given allopurinol as a positive control, group II was given aquades as control group negative, group III, IV and V were given extract of sea cucumber sand and potassium bromate as treatment group with concentration of 5%, 10%, and 15%. Result: The result of the research was analyzed quantitatively, showed that the extract of sea cucumber with 10% concentration was not significantly different with the extract of sea cucumber with concentration of 15%, when compared with the giving of sea cucumber extract with 5% concentration gave significantly different result with the giving of extract sea ​​cucumbers with concentrations of 10% and 15%. This shows the provision of sea cucumber extract with a concentration of 5% can give microscopic changes in the small intestine of mice due to exposure to potassium bromate. Conclusion: Sand cucumber extract (Holothuria scabra) with 5% concentration can give a change of histology picture of small intestine of mice (Mus muculus).